2019
DOI: 10.1136/bmjopen-2019-031415
|View full text |Cite
|
Sign up to set email alerts
|

Phase-out of smallpox vaccination and the female/male HIV-1 prevalence ratio: an ecological study from Guinea-Bissau

Abstract: ObjectiveIn Guinea-Bissau, West Africa, we observed that having a smallpox vaccination scar was associated with lower HIV-1 prevalence, more strongly for women than men. If this represents a causal effect, the female/male HIV-1 prevalence ratio would increase for birth cohorts no longer receiving smallpox vaccination due to the phase-out of this vaccine.DesignAn ecological design using HIV surveys and information about smallpox vaccination coverage.SettingUrban and rural Guinea-Bissau.ParticipantsParticipants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Although our findings do not allow for assumptions to be made about the mechanisms underlying the putative protective role of influenza vaccination on COVID-19 outcomes, previous immunological and epidemiological studies [35][36][37][38][39], as well as mathematical models [40][41][42], support the concept that vaccination against one microorganism may affect the host's response to other infectious agents. For example, vaccination against mycobacterium tuberculosis with the bacillus Calmette-Guérin vaccine significantly increases the secretion of IL-1B (a pro-inflammatory cytokine), which plays a recognized role in antiviral immunity [43].…”
Section: Discussionmentioning
confidence: 57%
“…Although our findings do not allow for assumptions to be made about the mechanisms underlying the putative protective role of influenza vaccination on COVID-19 outcomes, previous immunological and epidemiological studies [35][36][37][38][39], as well as mathematical models [40][41][42], support the concept that vaccination against one microorganism may affect the host's response to other infectious agents. For example, vaccination against mycobacterium tuberculosis with the bacillus Calmette-Guérin vaccine significantly increases the secretion of IL-1B (a pro-inflammatory cytokine), which plays a recognized role in antiviral immunity [43].…”
Section: Discussionmentioning
confidence: 57%
“…Furthermore, endemic cases in high-income countries declined greatly during the 1950s (9). Taken together, those data illustrate that smallpox vaccination coverage steadily declined in most high-income Western countries as smallpox was increasingly confined to low-income countries (7). Although an imported outbreak in Yugoslavia in 1972 caused 175 cases and 35 deaths, the last nonimported case in Europe was declared in 1953 (10); after that date, persons became less likely to receive smallpox vaccination.…”
mentioning
confidence: 90%
“…Although guidelines for recommended smallpox vaccination did not change during 1937–1980 in most countries in Europe, vaccination coverage in Spain and other countries declined continuously as disease eradication progressed ( 5 , 6 ). For example, a 2019 article reported that smallpox vaccination coverage in Guinea-Bissau fell dramatically during the 1970s, from 75% to 10%–25% ( 7 ). Another study, conducted in Denmark, reported that vaccination coverage dropped from 95% in 1965 to 5%–20% among persons born during the 1970s ( 8 ).…”
mentioning
confidence: 99%